Bioguided identification of daucosterol, a compound that contributes to the cytotoxicity effects of Crateva adansonii DC (capparaceae) to prostate cancer cells. (30th January 2020) - Zingue, Stéphane; Gbaweng Yaya, Abel Joël; Michel, Thomas; Ndinteh, Derek Tantoh; Rutz, Jochen; Auberon, Florence; Maxeiner, Sebastian; Chun, Felix K.-H.; Tchinda, Alembert Tiabou; Njamen, Dieudonné; Blaheta, Roman A.
Abstract: Ethnopharmacological relevance: Crateva adansonii DC (Capparaceae) is a shrub used to treat tumors in Cameroon. In our previous reports, a Crateva adansonii dichloromethane-methanol (DCM/MeOH) extract was shown to prevent chemically induced tumors in Wistar rats. Aim of study: To determine the bioactive principle of Crateva adansonii extract and to elucidate its underlying mechanism. Materials and methods: An activity-guided fractionation was realized using MTT assay. To investigate if the bioactive compound daucosterol (CA2) accounted for the previously observed anticancer effects of the C. adansonii extract, it was tested on cell growth, cell proliferation, cell cycle, cell death mechanism and cell migration. In addition, cell cycle- and apoptosis-regulating proteins were assessed by Western blotting. Results: Daucosterol (CA2), a steroid saponin, was identified as major anticancer principle of the C. adansonii extract. Daucosterol significantly inhibited LNCaP, DU145 and PC3 prostate carcinoma cell growth and proliferation at the optimal concentration of 1 μg/mL. It also significantly increased the number of late apoptotic (DU145) and apoptotic (PC3) cells. The number of cells in S phase increased in DU145, while the number of G0/G1 cells decreased. Cell cycle proteins (cdk1, pcdk1, cyclin A and B) were down-regulated in DU145 and PC3 cells, whereas only cdk2 was down-regulated in PC3 cells. Moreover, the anti-apoptotic Akt, pAKT and Bcl-2 proteins were down-regulated, while the pro-apoptotic protein Bax was up-regulated. CA2 induced anti-metastatic effects by decreasing chemotaxis and cell migration, while it increased cell adhesion to fibronectin and collagen matrix. Conclusion: These results suggest that daucosterol is the major active principle responsible at least in part for the anticancer effect of the extract of Crateva adansonii . Graphical abstract: Image 1